Borrowed time : Lennon's last decade [videorecording (DVD)] - Parker, Alan, 1965-; Morris, Alexa; Lennon, John, 1940-1980; Ono, Yōko; McCartney, Paul (Liverpool West Productions Inc., 2025)
Step into the life of a legend in this visionary new documentary exploring the final decade of John Lennon's life, with never-before-seen archive footage, interviews, and exclusive new stories. For the first time ever, the full story of how John and Yoko met is revealed, and watch as the curtain is lifted on the 1981 comeback tour that never came to be.